Analysis of Trace Metals in Hand Dug Wells around Dumpsites in Okene Metropolis, Nigeria - Folorunsho, Omeiza Samuel; Ojo, Adebayo Albert; Ayorinde, Adebayo Mathew; Olumuyiwa, Ajayi Olubode (Journal of Sustainability and Environmental Management, 2022)
This study examined the levels of trace metals in leachates from dumpsites and hand dug wells used as sources of drinking water by the inhabitants of Okene Metropolis, Kogi State Nigeria. This is important because the presence of toxic heavy metals in the environment continues to generate a lot of concern to environmental scientists, government agencies and public health practitioners leading to adverse health implications. The leachates and hand dug well water samples were collected during the wet season of 2019-2021 and analyzed for some selected trace metals (Cd, Cu, Ni, Pb, Zn, Cr, and Mn) using AA320N atomic absorption spectrophometer. The result showed that there was high concentration of most of the trace metals in the leachate samples compared to the groundwater samples with some of the trace metals above the maximum limit set by W.H.O. It is recommended that a systematic treatment of heavy metals concentration in hand dug well in the study area should be carried out regularly either through chemical precipitation, ion exchange or reverse osmosis.